Living Allergy Free How to Create and Maintain an Allergen- and Irritant-Free Environment - Gershwin, M. Eric; Klingelhofer, Edwin L. (Humana Press, 1992)
In this commonsense book, Dr. Gershwin and Dr. Klingelhofer offer sensible, practical strategies for identifying the substances that cause allergies (allergens), the symptoms they cause, ways exposure to allergens can be avoided or reduced, and ways you can relieve the symptoms. Living Allergy Free also treats some reactions that are commonly assumed to be allergies, but are really sensitivity or irritant reactions, shows how they can be distinguished from true allergies, and tells you what to do about them. If you suffer from allergies-or if you think you do-Living Allergy Free is just what the doctor would order!